Penerapan Differentiated Instruction dalam Meningkatkan Pemahaman Konsep Matematika Siswa Kelas 2 SD - Sion Stepani Simanjuntak; Tanti Listiani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Understanding concepts is one of the important things in learning Mathematics. However, in reality it was found that Grade 2 students had difficulty in understanding the concept of Mathematics. Therefore, in this study a strategy has chosen, namely Differentiated Instruction. The purpose of this study is to determine whether the application of Differentiated Instruction learning strategy can improve the understanding of the concept of class 2B students on Mathematics. The method carried out is the Classroom Action Research (CAR) by Robert Pelton with two cycles. The research was conducted at a Christian school in the West Jakarta area on September 26 to October 16, 2018, conducted with a total of 7 meetings. The instruments to collect data are lesson plans, mentor feedback, reflection journals, tests and documentation (photos). The results of the study shows that the Differentiated Instruction strategy can improve students' understanding of concepts on the three indicators used in this research. The maximum achievement of each indicator is restating a concept (72%), classifying objects based on certain characteristics according to the concept (100%), and presenting concepts in various forms of representation (80%). Differentiated Instruction can improve the understanding concept of, if each of the strategic steps are implemented properly. However, there are some things that need to be considered such as the emphasis on the concept of clear material, giving clear but simple instructions (for lower grade students), giving clear and firm rules, as well as variations in learning according to interests, learning styles, and student readiness.